PENGEMBANGAN APLIKASI DAILY ACTIVITY DI BPS PROVINSI KALIMANTAN UTARA - Annisa Yuli Pratiwi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Daily Activity is an application developed by BPS-Statistics of Sulawesi Tenggara Province. The application is then also applied in BPS-Statistics of Kalimantan Utara Province. In Daily Activity, employees report their daily activities, including the outputs. The list of activities is then manually summarized every month to form an Employee Performance Achievement Report (CKP). Because the process is still manual, the preparation of CKP reports has become less effective and efficient. Thus, the author tries to develop Daily Activity by adding the Employee Performance Achievement menu. The development uses the Software Development Life Cycle (SDLC) method with the waterfall approach. With this menu, now the list of activities can be summarized automatically by activity categories. The application has been tested with black-box testing to determine its functionality. The test results show that the application meets user needs in forming CKP reports.